Float up, sing down : stories - Hunt, Laird (Bloomsbury Publishing, 2024)
"Candy Wilson has forgotten to buy the paprika. Turner Davis needs to get his zinnias in. Della Dorner told her mother she was going to the Galaxy Swirl, but that's not where she's really headed on her new Schwinn five-speed. Float Up, Sing Down is the story of a single day. But in that day, how much teeming life! The residents of this rural town have their routines, their preferences, their joys, grudges, and regrets. Gossip is paramount. Lives are entwined. Retired sheriffs climb corn bins and muse on lost love, French teachers throw firecrackers out of barn windows, and teenagers borrow motorcycles to ride the back roads. Each of the fourteen stories of Float Up, Sing Down follows one character's "day-in-the-life" in one of Hunt's most beloved and enduring landscapes. In the tradition of Willa Cather, Sherwood Anderson, Elizabeth Strout, and Edward P. Jones, this is a symphony of souls, a masterful portrait of both loneliness and community by one of our great limners of American experience"--